Production of biodiesel by esterification of palmitic acid over mesoporous aluminosilicate Al-MCM-41 - Carmo, Alipio C.; de Souza, Luiz K. C.; da Costa, Carlos E. F.; Longo, Elson [UNESP]; Zamian, Jose R.; da Rocha Filho, Geraldo N. (Elsevier B.V., 2009)
Biodiesel has been obtained by esterification of palmitic acid with methanol, ethanol and isopropanol in the presence of Al-MCM-41 mesoporous molecular sieves with Si/Al ratios of 8.16 and 32. The catalytic acids were synthesized at room temperature and characterized by atomic absorption spectrometry (AAS), thermal analysis (TG/DTA), X-ray diffraction (XRD), nitrogen absorption (BET/BJH), infrared spectroscopy (IR), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The reaction was carried out at 130 degrees C whilst stirring at 500 rpm, with an alcohol/acid molar ratio of 60 and 0.6 wt% catalyst for 2 h. The alcohol reactivity follows the order methanol > ethanol > isopropanol. The catalyst Al-MCM-41 with ratio Si/Al = 8 produced the largest conversion values for the alcohols studied. The data followed a rather satisfactory approximation to first-order kinetics. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Mesoporous; Molecular sieves; Acid catalysts biodiesel; Esterification